Effect of organizational culture and work environment on employee performance of PT. POS Indonesia (Persero) East Jakarta - Faif Yusuf; Andrie Kurniawan; Ahmad Taufik (Journal of Economics and Business Letters, 2021)
Organizations that have organizational culture and a conducive work environment will show high employee performance as well. The problems that can be formulated from this research are: Is there any influence of organizational culture, work environment on employee performance at PT Pos Indonesia (Persero) East Jakarta. This study aims to determine the magnitude of the influence of organizational culture, work environment on employee performance either simultaneously or partially. The population in this study were all employees at PT Pos Indonesia (Persero) East Jakarta. Determination of the number of samples using random sampling technique, which then obtained the results of 53 respondents. Data collection tools used are documentation and questionnaires. The research data analysis method used instrument tests (validity test and reliability test), descriptive analysis of the percentage of classical assumption test, multiple regression analysis, partial hypothesis testing (t) and simultaneous test (F)., and coefficient of determination. The results of multiple linear regression analysis showed equation Y = 19.075 + 0.208 X1+ 0.336 X2. Partially the magnitude of the influence of each independent variable on the dependent variable, namely: Organizational culture of 17.7%, and work environment of 12.4%. Simultaneously the magnitude of the influence of work motivation and work environment on performance is 43.8%. The conclusion of this research is that there is an influence of organizational culture and work environment on employee performance at PT Pos Indonesia (Persero) East Jakarta simultaneously or partially.